Waterborne carbon nanotube ink for the preparation of electrodes with applications in electrocatalysis and enzymatic biosensing. (October 2018) - Garate, Octavio; Veiga, Lionel; Medrano, Anahí V.; Longinotti, Gloria; Ybarra, Gabriel; Monsalve, Leandro N.
Graphical abstract: Highlights: A water-based carbon nanotube ink was prepared and applied by rod coating as a single layer onto a flexible substrate. The printed layer was conductive, flexible and showed electrocatalytic behavior. The printed layer could be used as an enzymatic biosensor. The effect of oxygen plasma on electrical and electrochemical properties was studied. The fabrication of electrodes is fast and can be upscaled. Abstract: Conductive inks with optimal properties for amperometric sensor fabrication are key materials for low cost and high performance electrodes printed on flexible substrates. In this work, electrodes made with a carbon nanotube (CNT) waterborne ink were prepared and characterized. The electrodes showed mechanical stability and electrocatalytic behavior. Moreover, they were used for the immobilization of horseradish peroxidase (HRP) and their performance as enzymatic biosensors was assessed. Oxygen plasma treatment was used to generate carboxylic functionalities for enzyme immobilization. Its effect on the electrodes was investigated in order to optimize their performance. These electrodes were fabricated with an ink that provides a potentially simple route for roll-to-roll biosensor printing.